Foreign direct investment and environmental degradation in developing countries: Does the quality of institutions matter? - Ozioko, Paschal Nnaemezie; Abd Rahman, Muhammad Daaniyall; Mohamad, Wan Norhidayah; Abdulwakil, Muhammad Mansur (Human Resource Management Academic Research Society, 2023)
Most developing countries lack adequate financial resources to achieve their sustainable growth goals. As a result, developing countries, depend on foreign direct investment (FDI) to fill the gap. FDI flows have increased significantly around the world, especially in the last two decades to grow capital investment and competitiveness in host countries. Nonetheless, the surge in FDI raises concerns about its potential impact on environmental degradation. Most developing countries face serious environmental challenges because most of these countries are in transition where production activities and energy consumption exponentially rise, and access to cleaner environments and investment in environmental pollution abatement continues to be problematic. Therefore, this study examined the relationship between FDI and environmental degradation in 80 developing countries for the period 2000-2018 using Generalized Method of Moments (GMM) and Least Square Dummy Variable Corrected (LSDVC). The results indicate a positive relationship between FDI inflow and environmental degradation in developing countries. Furthermore, results suggest a significant positive relationship between FDI and environmental degradation in only middle-income countries when categorized into income groups. Interestingly, the magnitude of the impact reduces as the quality of institutions increases in these countries. In addition, results confirm a significant positive relationship between degradations and economic growth, energy usage, and population density. These results suggest that, while the negative impact of FDI does not necessitate concerted efforts to reduce it due to its enormous contribution to the economy, adequate efforts must be made to ensure that real FDI does not continue to contribute significantly to emissions.